ANALISIS PROGRES PENCAPAIAN MILLENIUM DEVELOPMENT GOALS PROVINSI JAWA TIMUR (Progress Analysis Of Achievement Millenium Development Goals In The Province Of East Java) - Roziana Ainul Hidayati (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
Problems of poverty alleviation is not an easy problem. Poverty alleviation programs should be targeted, the exact activities, the right program, the right location and the right budget. This programs will be undertaken in order to reduce poverty more in the form of charity, physical development and others that it is less well targeted. a lot of program-the program as activities which basically only be duplicated or copy paste from the previous year's activities with the intention that the budget, physical also often undertaken without first reviewing whether the local area is very requires the existence of the physical building while there are things another even more a priority for local residents to improve their welfare. And one of the frameworks that can help us understand poverty as a multidimensional problem and its measurement is with the Millennium Development Goals or also known as the Millennium Development Goals (MDGs). The results showed that the achievement of the MDGs progress in East Java of 7 (seven) existing Goal progress of his